Age-Related Decrease in Abdominal Pain and Associated Structural- and Functional Mechanisms: An Exploratory Study in Healthy Individuals and Irritable Bowel Syndrome Patients - Beckers, Abraham B.; Wilms, Ellen; Mujagic, Zlatan; Kajtár, Béla; Csekő, Kata; Weerts, Zsa Zsa R. M.; Vork, Lisa; Troost, Freddy J.; Kruimel, Joanna W.; Conchillo, José M.; Helyes, Zsuzsanna; Masclee, Ad A. M.; et al. (Frontiers in Pharmacology, 2021)
Introduction: The world population is ageing, resulting in increased prevalence of age-related comorbidities and healthcare costs. Limited data are available on intestinal health in elderly populations. Structural and functional changes, including altered visceroperception, may lead to altered bowel habits and abdominal symptoms in healthy individuals and irritable bowel syndrome (IBS) patients. Our aim was to explore age-related changes in gastrointestinal symptoms and underlying mechanisms. Methods: In total, 780 subjects (IBS patients n = 463, healthy subjects n = 317) from two separate studies were included. Subjects were divided into different age groups ranging from young adult to elderly. Demographics and gastrointestinal symptom scores were collected from all participants using validated questionnaires. A subset of 233 IBS patients and 103 controls underwent a rectal barostat procedure to assess visceral hypersensitivity. Sigmoid biopsies were obtained from 10 healthy young adults and 10 healthy elderly. Expression of the visceral pain-associated receptors transient receptor potential (TRP) Ankyrin 1 (TRPA1) and Vanilloid 1 (TRPV1) genes were investigated by quantitative RT-PCR and immunofluorescence. Results: Both elderly IBS and healthy individuals showed significantly lower scores for abdominal pain (p<0.001) and indigestion (p<0.05) as compared to respective young adults. Visceral hypersensitivity was less common in elderly than young IBS patients (p<0.001). Relative TRPA1 gene transcription, as well as TRPA1 and TRPV1 immunoreactivity were significantly lower in healthy elderly versus healthy young adults (p<0.05). Surprisingly, no significant association was found between the abdominal pain symptoms and the expression of the nociceptive ion channel expression. Conclusions: Our findings show an age-related decrease in abdominal pain perception. This may in part be related to decreased TRPA1 and/or TRPV1 receptor expression. Further studies are needed to reveal precise underlying mechanisms and the associations with intestinal health.